Utilization of Health Services Among Adults With Recurrent Clostridium difficile Infection: A 12-Year Population-Based Study. (20th October 2016) - Kuntz, Jennifer L.; Baker, Jennifer M.; Kipnis, Patricia; Li, Sherian Xu; Liu, Vincent; Xie, Yang; Marcella, Stephen; Escobar, Gabriel J.
Abstract : BACKGROUND: Considerable efforts have been dedicated to developing strategies to prevent and treat recurrent Clostridium difficile infection (rCDI); however, evidence of the impact of rCDI on patient healthcare utilization and outcomes is limited. OBJECTIVE: To compare healthcare utilization and 1-year mortality among adults who had rCDI, nonrecurrent CDI, or no CDI. METHODS: We performed a nested case-control study among adult Kaiser Foundation Health Plan members from September 1, 2001, through December 31, 2013. We identified CDI through the presence of a positive laboratory test result and divided patients into 3 groups: patients with rCDI, defined as CDI in the 14–57 days after initial CDI; patients with nonrecurrent CDI; and patients who never had CDI. We conducted 3 matched comparisons: (1) rCDI vs no CDI; (2) rCDI vs nonrecurrent CDI; (3) nonrecurrent CDI vs no CDI. We followed patients for 1 year and compared healthcare utilization between groups, after matching patients on age, sex, and comorbidity. RESULTS: We found that patients with rCDI consistently have substantially higher levels of healthcare utilization in various settings and greater 1-year mortality risk than both patients who had nonrecurrent CDI and patients who never had CDI. CONCLUSIONS: Patients who develop an initial CDI are generally characterized by excess underlying, severe illness and utilization. However, patients with rCDI experience even greater adverse consequences of their disease than patients who do not experience rCDI. Our results further support the need for continued emphasis on identifying and using novel approaches to prevent and treat rCDI. Infect Control Hosp Epidemiol. 2016;1–8